شیكردنەوەیەكی جیۆمۆرفۆلۆجی بۆ سەرهەڵدان و پەرەسەندنی دیاردەی گۆمەبەحری گەشتوگوزاری لە ناوچەی گەرمیان - رشید, شیروان عمر; امین, هێمن نصرالدین محمد (Sulaimani Journal for Humanities, 2021)
This Study is about Applied Geomorphology and Its relationship with tourism in Gomabahry karst phenomenon in Garmian area, with using Geographic information system )G.I.S(, to analyse morphometric properties of its watershed. The Gomabahry phenomenon located in maidan town concern to Khanaqeen District in Garmian administration southeastern Iraqi Kurdistan region in sub mountain area. Astronomically the Gomabahry phenomenon lies in the intersection of latitude (34° 49- 32=) north and longitude (45° 37- 49=) east, but the watershed is located between two latitudes (34° 43- 20= - 34° 50- 09=) north and longitudes (45° 36- 25= - 45° 42- 05=) east, with (55.09 km2) area, the upper part of the watershed is located on the Iraq-Iran international border. Based on the aim, the study was divided in to three sections (factors affecting the formation and development of Gomabahry phenomenon, Geomorphometric analysis of its watershed and tourism charachteristics of the area). The study came to the fact that the Gomabahry phenomenon is a karst phenomenon which is formatted due to external processes (Morphoclimatic processes), also its formation and development belong to Pliestocene epoch in Quaternary period, also the availability of water over the year and attractive features of the area caused to pull tourists especially population of Garmian area in lots of year months to recreational purpose like swimming and spend their leisure time despite lack of tourism services.